معرفی و بررسی نسخۀ خطی خلاصة المعارف از سید آدم بنوری: Introduction and Analysis of the Manuscript of Khulasat-al-Moarif by Sayyed Adam Binouri (Al-Aasar, 2025)
Manuscripts are considered the most valuable cultural and literary heritage of any nation. So, the restoration of these cultural resources is of great importance. The manuscript of the Khulasat-al-Moarif by Sayyed Adam Binouri is one of the valuable assets. This article focuses on the introduction and analysis of the manuscript and contribution of the author as well. Furthermore, the central themes, linguistic values, intellectual ideology, and literary features have also been evaluated. After having gone through the manuscript in depth, we can conclude that Sayyed Adam Binouri has written a valueable detailed work on the mysticism/ sufism and teachings of the Naqshbandiya school of thought, during his three years stay Makkah (1035-1037 AH). The manuscript is written in the simple language. The author has used the poetic examples of several other poets, in addition to his own, the Quranic verses, sayings of the Holy Prophet, and Sufis belonging to Naqshbandiya and other Sufi school of thoughts. The prose of book indicates an approach to popular culture, religious, moral and religious values. The author has given special attention to his significant style while expressing his thoughtful ideas and he has given in depth details of his specific ideology.